2008
DOI: 10.1017/s135561770808123x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of perceptual and motor inhibitory processes in young and elderly participants using the Simon task

Abstract: Deficits in inhibitory abilities are frequently observed in normal aging. However, few studies have explored the generality of these deficits in a single group of participants. Here, we used an adaptation of the Simon task to differentially assess perceptual and motor inhibition using the same stimuli and task design and to determine whether these processes use separate or shared cognitive resources. We were interested in determining whether (1) normal aging is associated with the use of separate (as previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 51 publications
8
30
0
2
Order By: Relevance
“…Ainsi par exemple, une distinction a été proposée entre des processus d'accès, de suppression et de restriction en mémoire de travail (Hasher, Tonev, Lustig, & Zacks, 2001;Hasher, Zacks, & May, 1999), entre des processus d'inhibition automatique et contrôlée (Nigg, 2000), et également entre des processus d'inhibition perceptive, motrice et linguistique (Dempster & Corkill, 1999 (Germain & Collette, 2008;Stawarczyk, Grandjean, Salmon, & Collette, 2012).…”
Section: Capacités D'inhibition Et Vieillissement Normalunclassified
See 1 more Smart Citation
“…Ainsi par exemple, une distinction a été proposée entre des processus d'accès, de suppression et de restriction en mémoire de travail (Hasher, Tonev, Lustig, & Zacks, 2001;Hasher, Zacks, & May, 1999), entre des processus d'inhibition automatique et contrôlée (Nigg, 2000), et également entre des processus d'inhibition perceptive, motrice et linguistique (Dempster & Corkill, 1999 (Germain & Collette, 2008;Stawarczyk, Grandjean, Salmon, & Collette, 2012).…”
Section: Capacités D'inhibition Et Vieillissement Normalunclassified
“…Nous avons également obtenu des données sous-tendant l'hypothèse de dédifférentiation du fonctionnement exécutif dans le domaine spécifique de l'inhibition (Germain & Collette, 2008). Plus précisément, nous avons tenté de déterminer si l'indépendance des processus d'inhibition perceptif et moteur précédemment observés chez des sujets jeunes (Nassauer & Halperin, 2003) est conservée lors du vieillissement normal.…”
Section: Les Déficits Exécutifs En Tant Que Conséquence D'un Processuunclassified
“…Although some studies did not confirm this effect (Wild-Wall et al, 2008; Salthouse, 2010; Hsieh et al, 2012), the most common finding was that older adults exhibited a stronger congruence effect on RTs than younger adults (West and Alain, 2000; Bialystok et al, 2004; Germain and Collette, 2008; Duchek et al, 2009). This effect was not due to a general slowing (van der Lubbe and Verleger, 2002; Maylor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for an age-related effect of congruence on accuracy is scarcer. Some studies have shown that older participants displayed a stronger congruence effect on errors (Proctor et al, 2005), but most studies have failed to find such an effect (van der Lubbe and Verleger, 2002; Germain and Collette, 2008; Duchek et al, 2009; Maylor et al, 2011). Furthermore, in the context of age-related effects, none of the above studies have distinguished impulsive selection from impulsive suppression according to the activation-suppression model, distinction which would give insights on the dynamics of cognitive action control.…”
Section: Introductionmentioning
confidence: 99%
“…The three tasks form a continuum of requirements for executive function from basic sensory/motor function (SRT), the integration of this with a choice decision (CRT), to the inhibition of a strong sensory-motor association during choice (interference task). The test parallels a manual reaction time test of perceptual inhibition (Nassauer and Halperin 2003; Germain and Collette 2008; Jennings et al 2011). In contrast with balance experiments that use a secondary dual task to divide attention, this study design integrates response inhibition function into the planning and execution of the postural task.…”
Section: Introductionmentioning
confidence: 99%